Eph/Ephrin-Based Protein Complexes: The Importance of cis Interactions in Guiding Cellular Processes - Cecchini, Alessandra; Cornelison, D. D. W. (Frontiers in Molecular Biosciences, 2022)
Although intracellular signal transduction is generally represented as a linear process that transmits stimuli from the exterior of a cell to the interior via a transmembrane receptor, interactions with additional membrane-associated proteins are often critical to its success. These molecules play a pivotal role in mediating signaling via the formation of complexes in cis (within the same membrane) with primary effectors, particularly in the context of tumorigenesis. Such secondary effectors may act to promote successful signaling by mediating receptor-ligand binding, recruitment of molecular partners for the formation of multiprotein complexes, or differential signaling outcomes. One signaling family whose contact-mediated activity is frequently modulated by lateral interactions at the cell surface is Eph/ephrin (EphA and EphB receptor tyrosine kinases and their ligands ephrin-As and ephrin-Bs). Through heterotypic interactions in cis, these molecules can promote a diverse range of cellular activities, including some that are mutually exclusive (cell proliferation and cell differentiation, or adhesion and migration). Due to their broad expression in most tissues and their promiscuous binding within and across classes, the cellular response to Eph:ephrin interaction is highly variable between cell types and is dependent on the cellular context in which binding occurs. In this review, we will discuss interactions between molecules in cis at the cell membrane, with emphasis on their role in modulating Eph/ephrin signaling.